An Overview of Systematic Reviews of Moxibustion for Knee Osteoarthritis - Yin, Shao; Zhu, Fengya; Li, Zhao; Che, Deya; Li, Liuying; Feng, Jie; Zhang, Lu; Huo, Zhenyi (Frontiers in Physiology, 2022)
AbstractBackground: Currently, many systematic reviews (SRs) of moxibustion as a treatment of KOA have been published. However, the evidence of different SRs of moxibustion to treat KOA has not been comprehensively evaluated.Aim: This overview aimed to evaluate the existing results and provide scientific evidence of the effectiveness and safety of moxibustion in the treatment of KOA. Methods: We conducted a comprehensive search of Embase, PubMed, Web of Science, Cochrane Library, SinoMed, CNKI, Wanfang, VIP and other databases until October 31, 2021. A Measurement Tool to Assess Systematic Reviews 2 (AMSTAR-2) was used to assess the methodological quality of SRs. Preferred Reporting Item for Systematic Reviews and Meta-Analyses was used to evaluate the reporting quality, and the risk of bias in SRs was evaluated by ROBIS Tool. We used the Grading of Recommendations Assessment, Development and Evaluation (GRADE) tool to determine the strength of evidence and conducted a meta-analysis of the total effectiveness rate. Results: Finally, 10 qualified SRs were included, including 57 randomised controlled trials and 5,149 participants. All SRs evaluated by AMASTAR-2 had more than one critical deficiency, so all SRs were rated as critically low. In the PRISMA checklist, the manuscript structures of the included SRs were relatively complete. Including four SRs with a low risk of bias and six with a high risk of bias using the ROBIS tool. In GRADE, two items (6.25%) were rated as high quality, three (9.37%) as medium quality, 17 (53.12%) as low quality and 10 (31.25%) as very low quality. A re-meta-analysis showed that moxibustion and moxibustion combined treatment improved the total effectiveness rate in knee osteoarthritis (risk ratio = 1.17, 95% confidence interval 1.13–1.21, P < 0.001 and risk ratio = 1.13, 95% CI 1.04–1.23, P < 0.001), with low heterogeneity (I2 = 36.3%, P = 0.020 and I2 = 0.0%, P = 0.956). A total of eight SRs reported adverse events, and no serious adverse events occurred in the moxibustion group and control group.